Modeling steel structures in OpenSees: Enhancements for fire and multi-hazard probabilistic analyses. (September 2015) - Elhami Khorasani, Negar; Garlock, Maria E.M.; Quiel, Spencer E.
Highlights: OpenSees-Thermal module is enhanced for fire and fire following earthquake analyses. OpenSees-Thermal module is modified to allow seamless seismic and thermal analyses. OpenSees-Thermal module is adjusted to perform reliability analysis. Examples show application of thermal module and reliability analysis in OpenSees. Abstract: Fire and post-earthquake fires pose a major hazard to our built environment with possible catastrophic consequences. Any framework developed for evaluating the resilience of steel structures in a multi-hazard context should incorporate tools that are capable of probabilistic structural analyses under fire and seismic loads. With a newly added thermal module, the OpenSees software has the capacity to perform structural analysis for the effects of cascading seismic and fire events. This paper presents modifications to the current source code that enable post-earthquake fire analysis for steel structures, and the enhancement to adapt reliability analysis in the thermal module.